Fibro-osseous pseudotumor of the digit. - Miotto, G.; Cimmino, A.; Bonifazi, E. (European Journal of Pediatric Dermatology, 2013)
The fibro-osseous pseudotumor of the digit (1, 2, 3) is a rare non-neoplastic condition of heterotopic ossification that affects the soft tissues of the fingers and which has the same significance as localized myositis ossificans (3), i.e. a reactive, benign myofibroblastic and osseous proliferation. It prevails in the young adult and in females, usually involving the fingers (3), especially the proximal phalanx of the index (3), sometimes the feet, rarely other sites, such as the frontal region (2). A proportion of patients reports a trauma, sometimes repetitive, in our case nail biting. The radiological examination shows, as in our case, the integrity of the phalangeal bone profile and a soft-tissue swelling with indistinct limits within which are located focal calcification without the typical appearance of the zonal myositis ossificans; the latter consists of a trasparent area in the center of the lesion, which indicates the formation of immature bone, surrounded peripherally by a dense zone of mature ossification. The histological examination, as in our case, shows bundles of spindle cells, with minimal or mild atypia, immersed in a myxoid stroma containing irregular osteoid trabeculae delimited by osteoblasts. The removal of the lesion is rarely followed by local recurrences. It is important to know the clinical, radiological and histological features of this condition, especially to distinguish it from malignat conditions as extraskeletal osteosarcoma, which affects mainly the elderly and presents cytological atypia and atypical mitosis (2).